Serenity Harbor [large type] - Thayne, RaeAnne (Thayne, RaeAnne. Haven Point, 2017)
"When Katrina Bailey helps an autistic child avoid a meltdown in the grocery store, his older half-brother offers her twelve thousand dollars to be Milo's temporary nanny until the specialist he's hired arrives. The money will bring her closer to her adoption goal, but how will she protect her heart from the lovable Callahan brothers?"--